A Comparison Of Performances Of Spiral Concentrators Having Different Geometries - D. Gucbilmez (International Mineral Processing Congress, 2012)
Three spiral concentrators having different geometries were compared in a chromite processing plant. They had different diameters, helix-cross sections and capacities. Two of the spiral concentrators were manufactured in China and one of them was manufactured in Australia. The tests were carried out in a closed circuit experimental setup by using a low grade chromite ore. The pulp densities kept the same during the operation, and the samples were taken simultaneously. The effects of the different positions of the splitters on separation and the feed rate were the parameters that were observed during the experiments. The performances of three spiral concentrators were found to be different. To clarify the effect of the particle size on the separation in spiral concentrators, the screening was applied to the feed. The samples were sieved from 75µm. The test results indicated that the separation performance decreased dramatically in very fine particles. Although fine particles caused some problems in spiral concentrators, fine grinding is required for this particular chromite ore for better liberation. A suitable method for the fine particles should be investigated for acceptable recovery.